The reduviid genus Nagustoides Miller (Heteroptera: Reduviidae: Harpactorinae) found in China, with description of a new species - Zhao, Ping; Cai, Wanzhi; Ren, Dong (Zootaxa, 2006)
The genus Nagustoides Miller, 1954 is recorded for the first time from China. Nagustoides lii is described as new to science. A key to the species of genus is provided. The diagnostic characters of the genus Nagustoides are revised. The abnormal venation of left fore wing of a female is noted. The type specimens are preserved in the Entomological Museum of China Agricultural University, Beijing.